Fertilizer and Sustainable Intensification in Africa - Stein T. Holden (Norwegian University of Life Sciences (NMBU), Centre for Land Tenure Studies (CLTS), 2018)
The paper investigates the important role of fertilizer to enhance sustainable intensification and food security in Sub-Saharan Africa based on a multi-disciplinary literature review. The review starts with a macro-perspective taking population growth, economic development and climate change into account. This is complemented with a micro-perspective summarizing findings from comprehensive micro-data in selected African countries. Agronomic, environmental and economic profitability implications of fertilizer use are reviewed. An assessment is made whether small farmers in Africa should be considered rational or partly irrational agricultural decision-makers and whether this can affect fertilizer use. I then discuss some controversial and promising policy approaches that may have the potential to enhance sustainable intensification and nutrient use efficiency in African agriculture before I conclude.
Keywords: Q12; Q18; Q56; 330; Sub-Saharan Africa; fertilizer; sustainable intensification; food security; policy